Construction of Te-ZnO@S-g-C3N4 Heterojunction Nanocomposites for the Efficient Removal of Methylene Blue, Antifungal Activity, and Adsorption of Cr(VI) Ion - Komal Aroosh; Mohsin Javed; Nadia Hussain; Ahmad Alhujaily; Shahid Iqbal; Mohammed T. Alotaibi; Muhammad Faizan; Muhammad Shuaib Khan; Ali Bahadur; Muhammad Abdul Qayyum; Nasser S. Awwad; Yosef Jazaa; et al. (Adsorption Science & Technology)
Heterojunctions have proven to be effective catalysts for removing organic pollutants and heavy metals from wastewater. The following study is also about the formation of 2D heterojunction tellurium-doped zinc oxide composite with sulfur-doped graphitic carbon nitride (Te-ZnO@S-g-C3N4) by adopting a low-cost, simple, and ecofriendly coprecipitation technique. Thiourea was calcined to prepare S-g-C3N4 using the thermal degradation method. The characterization of synthesized photocatalysts was carried out by using SEM-EDX, FTIR, and XRD. The results obtained showed that the incorporation of tellurium caused an alteration in the wurtzite structure of ZnO. SEM-EDX analysis validated the purity of the synthesized samples due to the absence of any additional peaks. The decrease in the bandgap was also noted by the formation of composites. Using methylene blue as a reference dye, the UV-vis spectrophotometer was utilized to calculate the absorbance for photocatalytic degradation behavior. As a result of tellurium doping into the ZnO lattice, photocatalytic oxidation/reduction was improved, according to the results. 3Te-ZnO NPs showed the best degradation rate among dopant series, while an excellent overall degradation rate was noted by fabricated composite 3Te-ZnO@40S-g-C3N4. The best doped ZnO and composites were also used as sorbents for the abstraction of heavy metal (Cr(VI)) from water via adsorption. A definite rise in the removal efficiency percentage of chromium ions was observed by using these sorbents. The overall photo degradation rate and adsorption behavior noted were in ZnO<Te-ZnO<Te-ZnO@S-g-C3N4 order. When compared to ZnO, Te-ZnO, SCN, and Te-ZnO@40SCN, the 3Te-ZnO@40SCN NCs have outstanding antifungal potential. The improved dispersibility and interaction of 3Te-ZnO@40SCN with membrane and intracellular proteins of fungi may be the cause of the greater effect of Te-ZnO@40SCN.